Evaluation of Organic and Inorganic Sources of Nutrients on Yield and Quality of Snake Gourd. (Trichosanthes anguina L) - Phebe Joseph (Department of Agronomy, College of Agriculture, 1998)
An experiment was conducted at the Instructional Farm attached to the College of Agriculture, Vellayani during January to May 1997 with the objectives of finding out the potential of using farmyard manure, poultry manure, vermicompost and fertilizers and the extend to which organic manures can be substituted for fertilizers for increasing yield and improving the quality of snake gourd (Trichoso/hes anguina L.). Three sources of organic manures, three levels of chemical fertilizers and three additional treatments (organic sources + organic sources to substitute NPK) were tested for their efficiency in 3 X 3 + 3 factorial RBD with three replications. The results of the study revealed that yield attributing characters like length of the fruit, weight of the fruit and number of fruits per plant were highest in plots applied with farmyard manure + farmyard manure to substitute